Diagnostic and Surgical Outcomes for Pediatric Hernias : A Literature Review - Wahyu Agus Prastyo; Artha Investari Nugraheni (International Medical Journal Corp. Ltd, 2025)
Introduction: The literature on pediatric hernias and their surgical management has seen significant advancements, particularly in the comparison between laparoscopic and traditional open repair techniques. Literature Review : Research has highlighted various advantages of laparoscopic repair, such as shorter recovery times and reduced postoperative pain (Namgoong et al., 2014). However, concerns regarding recurrence rates and operational costs persist, prompting further investigation into the nuances of different surgical approaches (Min Lim et al., 2020). A retrospective study reinforced the notion that while laparoscopic techniques offer enhanced visibility and potential cosmetic benefits, open repair remains a reliable standard due to its simplicity and established success rates (N. Al-Taher et al., 2021). The growing body of literature underscores the importance of minimally invasive surgery (MIS) in pediatric settings, with bibliometric analyses indicating a trend towards laparoscopic techniques, particularly in cases of bilateral hernias and recurrences (Shu et al., 2022). Recent contributions have advocated for personalized surgical approaches that prioritize patient recovery and safety, reflecting an evolution in hernia repair methodologies. Conclusion: Collectively, the literature illustrates a robust discourse surrounding pediatric hernia repair, where the ongoing evaluation of laparoscopic techniques against traditional methods is paramount. The findings indicate that while laparoscopic approaches are gaining traction, a balanced perspective that considers both the potential benefits and the established efficacy of open repair is essential for informed surgical decision-making in pediatric patients.